Tauroursodeoxycholic acid prevents Bax-induced membrane perturbation and cytochrome C release in isolated mitochondria - Rodrigues, Cecília M. P. (2013)
Biochemistry, 2003, 42 (10), pp 3070–3080 DOI: 10.1021/bi026979d